[1, 4]‐S‐ to O‐Silyl Migration: Multicomponent Synthesis of α‐Thioketones through Chemoselective Transformation of Esters to Ketones with Organolithium Reagents. Issue 51 (14th November 2013) - Sun, Xianwei; Song, Zhenlei; Li, Hongze; Sun, Changzheng
Abstract A [1, 4]‐S‐ to O‐silyl migration has been exploited to chemoselectively transform esters into ketones by using organolithium reagents, allowing multicomponent synthesis of α‐thioketones. Mechanistic studies reveal that this migration proceeds in an intramolecular manner and is more favorable than the corresponding [1, 5]‐S‐ to O‐ and [1, 3]‐C‐ to O‐silyl migrations. The resulting α‐thioketones are valuable building blocks for the synthesis of cyclic or multifunctionalized organosulfur compounds.